2006
DOI: 10.1093/geronb/61.4.p228
|View full text |Cite
|
Sign up to set email alerts
|

Handwriting Process Variables Discriminating Mild Alzheimer's Disease and Mild Cognitive Impairment

Abstract: This study's aims were (a) to examine kinematically the handwriting process of persons with mild cognitive impairment (MCI), compared with those with mild Alzheimer's disease and healthy controls; (b) to assess the importance of these measures for the differentiation of the groups; and (c) to assess characteristics of the handwriting process across different functional tasks. Thirty-one persons with MCI, 22 with mild Alzheimer's disease, and 41 healthy controls performed functional tasks while using a computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
103
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(122 citation statements)
references
References 30 publications
16
103
0
3
Order By: Relevance
“…Our research hypotheses were that differences would be found between writing under high and under low mental workload, with pressure, temporal, angular velocity, and spatial measures obtained by a computerized system. On the basis of previous results concerning detection of clinical pathologies and deception (Luria & Rosenblum, 2010;Werner et al, 2006), we predicted that writing under high mental workload would affect both handwriting measures (the mean values of each measure) and their variability (the SD values of each measure). However, because there was very little information about the effects of mental workload on the handwriting behaviors measured in this study (when numbers rather than words and sentences were written), we hypothesized differences between handwriting measures with no specific direction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research hypotheses were that differences would be found between writing under high and under low mental workload, with pressure, temporal, angular velocity, and spatial measures obtained by a computerized system. On the basis of previous results concerning detection of clinical pathologies and deception (Luria & Rosenblum, 2010;Werner et al, 2006), we predicted that writing under high mental workload would affect both handwriting measures (the mean values of each measure) and their variability (the SD values of each measure). However, because there was very little information about the effects of mental workload on the handwriting behaviors measured in this study (when numbers rather than words and sentences were written), we hypothesized differences between handwriting measures with no specific direction.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that a computerized system of objective measures of the handwriting process may be sensitive to dis-automatization (e.g., Teulings, 2001;Tucha, Laufkotter, Mecklinger, Klein, & Lange, 2001;Werner, Rosenblum, Bar-On, Heinik, & Korczyn, 2006). Specifically, it has been found that such computerized measures are sensitive to cognitive deterioration during the various stages of Alzheimer's disease .…”
Section: Introductionmentioning
confidence: 99%
“…Toutes ces personnes ont été invitées à copier, sur une tablette Wacom, un numéro de téléphone, une liste d'articles d'épicerie (mots), à remplir un chèque, à copier les lettres de l'alphabet hébreu, ainsi qu'un paragraphe de 107 caractères [5].…”
Section: Etat De L'artunclassified
“…Handwriting signals have been used for cognitive impairment detection. For instance, handwriting skill degradation and Alzheimer's disease (AD) appear to be significantly correlated (Forbes, Shanks and Venneri, 2004) and some handwriting aspects can be good indicators for its diagnosis (Neils-Strunjas et al, 2006) or help differentiate between mild Alzheimer's disease and mild cognitive impairment (Werner et al, 2006). As demonstrated in Faundez- , the visual inspection of the pen down images suggest a progressive degree of impairment, where drawing becomes more disorganized and the three dimensions effect of the drawing (a house) is only achieved in the mild case.…”
Section: Handwritingmentioning
confidence: 99%